2020
DOI: 10.1016/j.omtn.2019.10.007
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Silencing Long Non-coding RNA LINC01224 Inhibits Hepatocellular Carcinoma Progression via MicroRNA-330-5p-Induced Inhibition of CHEK1

Abstract: Hepatocellular carcinoma (HCC) accounts for approximately 85%-90% of primary liver cancers. Based on in silico analysis, differentially expressed long non-coding RNA (lncRNA) LINC01224 in HCC, the downstream microRNA (miRNA) miR-330-5p, and its target gene checkpoint kinase 1 (CHEK1) were selected as research subjects. Herein, this study was designed to evaluate their interaction effects on the malignant phenotypes of HCC cells. LINC01224 and CHEK1 were upregulated and miR-330-5p was downregulated in HCC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 34 publications
5
67
0
Order By: Relevance
“… 11 LINC01224 could up-regulate the expression of CHEK1 by competitively binding to miR-330-5p, thus promoting hepatocellular carcinoma development. 10 In the present study, similar to the previous studies, we found that the expression of LINC01224 was significantly increased in CRC tissues and cell lines. Moreover, in vitro analysis demonstrated that LINC01224 silence suppressed cell proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 11 LINC01224 could up-regulate the expression of CHEK1 by competitively binding to miR-330-5p, thus promoting hepatocellular carcinoma development. 10 In the present study, similar to the previous studies, we found that the expression of LINC01224 was significantly increased in CRC tissues and cell lines. Moreover, in vitro analysis demonstrated that LINC01224 silence suppressed cell proliferation and invasion.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that LINC01224 promoted hepatocellular carcinoma progression through microRNA-330-5p-induced inhibition of CHEK1. 10 Moreover, Xing et al reported that LINC01224 exhibited cancer-promoting activity in EOC (epithelial ovarian cancer) through microRNA-485-5p-mediated PAK4 upregulation. 11 However, the biological function and underlying mechanism of LINC01224 in the development of human cancer, including CRC are still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Checkpoint kinase1 (CHEK1), one of the DNA-damage checkpoint proteins, was reported reducing the stem cell population in ovarian cancer, triggered by its inhibitor (LY2603618) [46]. In hepatocellular carcinoma (HCC), downregulation of CHEK1 by silencing LINC01224 or elevating miR-330-5p could inhibit stemness, by reducing the expression of CSC biomarkers (OCT4, CD133 and SOX2) [47]. The genes of CDC45, ESPL1, CCNA2, MCM6, and ORC1 have not been reported on the CSC issues in our survey.…”
Section: Discussionmentioning
confidence: 99%
“… [33] Gong et al found that LINC01224 regulated the expression levels of CHEK1 by competitively binding to miR-330-5p, thus inhibiting hepatocellular carcinoma progression. [34] LINC00668 is overexpressed in BC tissues and contributes to the progression of BC by accelerating cell cycle progression and inhibiting cell apoptosis. [35] In view of the outstanding performance of prognostic prediction, the roles of these lncRNAs in cancers should be investigated in the future, especially for BC.…”
Section: Discussionmentioning
confidence: 99%